Determination of Azithromycin by an alternative FIA amperometric method for different pharmaceutical applications - Pfaffen, Maria Valeria del Valle (2013)
This work presents a fast and reliable electroanalytical procedure for the quantification of azithromycin (AZ) in different systems that couples flow injection analysis and amperometric detection (FIA-AM). The quantification was performed at a working potential of 1.20 V (vs Ag/AgCl/NaCl (3 M)) in 0.05 M phosphate buffer at a flow rate of 1.0 mL min−1 . Under these conditions a 1.00 × 10−6 −1.50 × 10−5 M linear range, (5.8 ± 0.4) × 104 CAZ (μA M −1 ) sensitivity and 4.44 × 10−7 M limit of detection are obtained. Also, this technique can be used without sample pretreatment and presents good reproducibility. The procedure was applied to the determination of the content of AZ in commercial tablets, to study the intrinsic dissolution rate of compacts of AZ dihydrate, and to determine the AZ release from a AZ hydrogel and carbomer. The method was statistically analyzed and proves to be reliable and robust. However, more remarkable is that FIA-AM technique presents better sensitivity and high sampling rate.